Volume 2: 42nd Computers and Information in Engineering Conference (CIE) 2022
DOI: 10.1115/detc2022-89187
|View full text |Cite
|
Sign up to set email alerts
|

Framework Design of a Digital Twin of an XY Compliant Parallel Manipulator Based on Non-Negative Matrix Factorization

Abstract: A promising multi-layer mirror-symmetry XY compliant parallel manipulator (CPM) has been recently reported to address the tradeoff between a small compact footprint and a minimized parasitic rotation. In order to scientifically ensure the healthy operation of equipment and make maintenance decisions reasonably, there is a need to depict its physical mechanical characteristics in a virtual space instantaneously. The digital twin, an emerging technology, can be used to address this need by achieving a seamless c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several authors used (interconnected) flow and decision diagrams to model the behaviour of the product [ 191 , 192 ]. Christofi and Pucel [ 193 ] described the behaviour of a product using fault trees and behaviour trees, while Negri et al [ 194 ] used the identified states (idle, working, error, emergency button, and energy-saving mode) of the product to model it.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors used (interconnected) flow and decision diagrams to model the behaviour of the product [ 191 , 192 ]. Christofi and Pucel [ 193 ] described the behaviour of a product using fault trees and behaviour trees, while Negri et al [ 194 ] used the identified states (idle, working, error, emergency button, and energy-saving mode) of the product to model it.…”
Section: Resultsmentioning
confidence: 99%